Nilai pH, VFA dan NH3 Silase Jerami Padi Yang Dibuat Dengan Penambahan Tepung Porang (Amorphophallus muelleri) Secara In Vitro - Mafefa, N. C.; Manu, A. E.; Nikolaus, T. T. (Universitas Bengkulu, 2023)
This study aims to determine the pH, VFA and NH3 values of rice straw silage made with the addition of Porang flour additives. Research and silage analysis was conducted at the Faculty of Maritime Animal Husbandry and Fisheries, University of Nusa Cendana, Kupang. The design in this study was a Completely Randomized Design (CRD) with four treatments and four replications. Treatment P0 (rice straw silage without Porang flour additive) as control, P1 treatment (rice straw silage with 3% Porang flour additive), P2 (rice straw silage with 6% Porang flour additive) and P3 (rice straw silage with 9% Porang flour additive). The observed variables were pH, VFA and NH3. The data obtained were analyzed using analysis of variance and Duncan's multiple range test. The results showed that all treatments had a significant effect (P<0.01) on pH, VFA and NH3 values. The pH values ranged from 3.78 – 5.48, the total VFA values ranged from 61.13 mM – 86.06 mM, and the NH3 values ranged from 5.88 mM – 9.50 mM. As a result, adding Porang flour (Amorphophallus muelleri) as an additive in rice straw silage up to 9% significantly lowered the pH value and increased the VFA and NH3 values.